Exposure to Ambient Ultrafine Particles and Nitrogen Dioxide and Incident Hypertension and Diabetes. Issue 3 (May 2018) - Bai, Li; Chen, Hong; Hatzopoulou, Marianne; Jerrett, Michael; Kwong, Jeffrey C.; Burnett, Richard T.; van Donkelaar, Aaron; Copes, Ray; Martin, Randall V.; Van Ryswyk, Keith; Lu, Hong; Kopp, Alexander; et al.
Abstract : Background: Previous studies reported that long-term exposure to traffic-related air pollution may increase the incidence of hypertension and diabetes. However, little is known about the associations of ultrafine particles (⩽0.1 μm in diameter) with these two conditions. Methods: We conducted a population-based cohort study to investigate the associations between exposures to ultrafine particles and nitrogen dioxide (NO2 ) and the incidence of diabetes and hypertension. Our study population included all Canadian-born residents aged 30 to 100 years who lived in the City of Toronto, Canada, from 1996 to 2012. Outcomes were ascertained using validated province-wide databases. We estimated annual concentrations of ultrafine particles and NO2 using land-use regression models and assigned these estimates to participants' annual postal code addresses during the follow-up period. Using random-effects Cox proportional hazards models, we calculated hazard ratios (HRs) and 95% confidence intervals (CIs) for ultrafine particles and NO2, adjusted for individual- and neighborhood-level covariates. We considered both single- and multipollutant models. Results: Each interquartile change in exposure to ultrafine particles was associated with increased risk of incident hypertension (HR = 1.03; 95% CI = 1.02, 1.04) and diabetes (HR = 1.06; 95% CI = 1.05, 1.08) after adjusting for all covariates. These results remained unaltered with further control for fine particulate matter (⩽2.5 μm; PM2.5 ) and NO2 . Similarly, NO2 was positively associated with incident diabetes (HR = 1.06; 95% CI = 1.05, 1.07) after controlling for ultrafine particles and PM2.5 . Conclusions: Exposure to traffic-related air pollution including ultrafine particles and NO2 may increase the risk for incident hypertension and diabetes. See video abstract at, http://links.lww.com/EDE/B337 . Abstract : Supplemental Digital Content is available in the text.